The Effect of Triage on Occupational Health at the Kembangan Hospital during the Covid19 Pandemic - Yuliati Yuliati; Kezia Irene Joseph (Jurnal Keperawatan Galuh, 2022)
Introduction: Corona Virus Disease or also known as COVID-19 has become a major global health problem. Health workers are one of the groups most vulnerable to being exposed to SARS-CoV-2, so to protect occupational health from health workers, triage during the COVID-19 pandemic can play a key role. Recommendations for triage implementation have been issued in Indonesia and all hospitals need to implement the protocol, one of the government hospitals in the West Jakarta area is RSUD Kembangan. Further evidence is needed to prove that triage has an impact on the occupational health of health workers during the COVID-19 pandemic. The purpose of this study was to identify the effect of triage implementation on the health of health workers during the COVID-19 pandemic at Kembangan Hospital. This study used an associative design with a cross sectional method. This study used a total sampling technique, so the sample used in the study was the entire population, namely 27 health workers who worked in the triage area of Kembangan Hospital. The instruments used in the study were questionnaires and observation instruments. Validity and reliability tests were carried out at the Kebon Jeruk Health Center and found valid and reliable results. This study found the conclusion that there was an effect of implementing triage on the health of health workers during the COVID-19 pandemic at Kembangan Hospital